2021
DOI: 10.1021/acs.jpcc.1c01019
|View full text |Cite
|
Sign up to set email alerts
|

DFT + U Study of Strain-Engineered CO2 Reduction on a CeO2–x (111) Facet

Abstract: Ceria is a promising material for cathodes in hightemperature CO 2 electrolysis cells because ceria can become a mixed electronic and ionic conductor through doping, which enables a high surface area for electrocatalysis. Here, we systemically investigate the effect of strain to enhance the activity for electrocatalytic CO 2 RR on CeO 2 (111) using density functional theory corrected for on-site Coulomb interactions (DFT + U). We find that tensile strain decreases the oxygen vacancy formation energy due to a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Because of a strong repulsion between the surface oxygen atoms and the newly formed O*, this is feasible on oxygen-deficient surfaces. Kildgaard et al studied this reaction on CeO 2– x (111) and found that carbonate cannot decompose to CO because of a prohibitively high activation barrier, whereas the less stable bidentate CO 2 – could decompose with a barrier of 0.57 eV . Similarly, CeO 2 (110) is conducive for this reaction only when oxygen vacancies are represent.…”
Section: Resultsmentioning
confidence: 99%
“…Because of a strong repulsion between the surface oxygen atoms and the newly formed O*, this is feasible on oxygen-deficient surfaces. Kildgaard et al studied this reaction on CeO 2– x (111) and found that carbonate cannot decompose to CO because of a prohibitively high activation barrier, whereas the less stable bidentate CO 2 – could decompose with a barrier of 0.57 eV . Similarly, CeO 2 (110) is conducive for this reaction only when oxygen vacancies are represent.…”
Section: Resultsmentioning
confidence: 99%
“…S1a (ESI †), the open circuit voltage (OCV) is 0.82 V lower than 1.0 V for fuel cells employing NCA as the anode because commercial cerium oxide is a mixed ionic and electronic conductor in a reducing atmosphere. 23 Moreover, the electrolyte has not been sintered at high temperature and thus some OCV losses is possibly caused by gas leakage. However, the OCV is over 1.0 V for the cell employing NCAL as the anode, indicating that the electronic conductivity and gas leakage problem are eliminated, which may be owing to the in situ formed LiOH coating on the surface of cerium oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Among van der Waals corrections, we selected the DFT-D2 method proposed by Grimme . Considering the on-site Coulomb repulsion between d orbital electrons, we applied the Hubbard U corrections to transition metal d electrons, and the values of the U-J parameters were 4.5 eV for Ce atoms, 4 eV for Ti atoms, 6 eV for Cu atoms, 3.8 eV for Fe atoms, and 6.6 eV for Ni atoms . After convergence test calculations, we set the plane-wave basis kinetic energy cutoff to be 700 eV, and the Brillouin zone was sampled by a Monkhorst–Pack k -point mesh of 1 × 1 × 1.…”
Section: Methodsmentioning
confidence: 99%